Disparities in Norms and Practices of Authority for Managing Public Street Lighting - Muhammad Syarifi Qolbi; Radian Salman; Rosa Ristawati (Universitas Lambung Mangkurat, 2025)
This study examines the legal legitimacy of the delegation of authority for managing Public Street Lighting (PJU) from the provincial government to district/city governments. This delegation often occurs without the support of clear legal norms, thus giving rise to issues of legality, accountability, and clarity of the authority structure between levels of government. This study uses a socio-legal approach with normative analysis techniques based on the legitimacy theory of French and Raven and the systemic legal theory of H.L.A. Hart. The research location focused on Pasuruan Regency. The results of the study indicate that the district government's authority in handling PJU is still functional without adequate legal legitimacy, and is not supported by a strong system of coordination and institutional recognition. This condition reflects the weak integration between the legal structure and administrative implementation, which impacts the effectiveness of services and legal certainty in PJU governance.